Use of Material-Shape Factors in Mechanical Design - Hrdlicka, Filip; Kratochvil, Martin; Mazinova, Ivana; Florian, Pavel (Manufacturing Technology Journal, 2019)
During design process materials and their shapes selection is usually performed unsystematically, selection is mostly based on previous experience, although this is the most influencing part during mechanical design. This paper is devoted to the application of the material-shape factors and indexes to the standard bicycle frame. Paper to show the method with material-shape factors and indexes and how to use it for a simply and fast redesign for a different material and shapes. The whole method is descripted in detail for two examples and the results are verified by FEM analysis.
Keywords: shape factor; material index; optimization; mechanical design